Governing Modern Societies - Stehr, Nico; Ericson, Richard V., 1948-2007 (Book collections on Project MUSE., 2000)
The essays collected in Governing Modern Societies arose from a lecture series of the same name held at Green College, University of British Columbia, in 1997 and 1998.